1994
DOI: 10.1128/mcb.14.12.8123
|View full text |Cite
|
Sign up to set email alerts
|

Erythroid cell-specific determinants of alpha-globin mRNA stability.

Abstract: Although globin mRNAs are considered prototypes of highly stable messages, the mechanisms responsible for their longevity remain largely undefined. As an initial step in identifying potential cis-acting elements or structures which contribute to their stability, we analyzed the defect in expression of a naturally occurring a2-globin mutant, aConstant Spring (CS). The CS mutation is a single-base change in the translation termination codon (I!AA-WCAA) that allows the ribosome to read through into the 3' nontran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
147
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(154 citation statements)
references
References 59 publications
7
147
0
Order By: Relevance
“…In addition, several studies have revealed that a number of variables need to be considered in the interpretation of mRNA stability data, including the effect of translation on mRNA turnover (Savant-Bhonsale and Cleveland, 1992;Nishizawa and Okamoto, 1994;Chen et al, 1995). For example, minor changes in mRNA sequence, because of the introduction of point mutations or specific deletions, may affect mRNA stability indirectly via a perturbation of the RNA secondary structure that leads to changes in translation efficiency (Weiss and Liebhaber, 1994). In view of this potential problem, we examined the ability of different 3Ј UTR deletion mutants used in this study to generate GAP-43 protein in transfected cells and found that all of them were translated effectively.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, several studies have revealed that a number of variables need to be considered in the interpretation of mRNA stability data, including the effect of translation on mRNA turnover (Savant-Bhonsale and Cleveland, 1992;Nishizawa and Okamoto, 1994;Chen et al, 1995). For example, minor changes in mRNA sequence, because of the introduction of point mutations or specific deletions, may affect mRNA stability indirectly via a perturbation of the RNA secondary structure that leads to changes in translation efficiency (Weiss and Liebhaber, 1994). In view of this potential problem, we examined the ability of different 3Ј UTR deletion mutants used in this study to generate GAP-43 protein in transfected cells and found that all of them were translated effectively.…”
Section: Discussionmentioning
confidence: 99%
“…It has long been noted that certain RNA-binding proteins can be characterized, grouped, and purified on the basis of their binding to nucleic acid homopolymers (Swanson & Dreyfuss, 1988)+ A defined set of RNAbinding proteins is characterized by high affinity and sequence-specific interaction with poly(C)+ These poly(C)-binding proteins (PCBPs) comprise two subsets in mammalian cells; hnRNPs K/J (Matunis et al+, 1992) and the aCP proteins (a-complex proteins)+ The exact structural and genetic relationship of hnRNP K and J remains to be fully defined+ The aCPs are encoded at four dispersed loci, with additional isoforms generated via alternative splicing (Makeyev & Liebhaber, 2000)+ The PCBPs studied in greatest detail are hnRNP K, aCP-1, and aCP-2+ The latter two proteins are alternatively referred to as PCBP1 and PCBP2 or hnRNP-E1 and hnRNP-E2 (Kiledjian et al+, 1995;Leffers et al+, 1995)+ Recent studies, summarized in this review, reveal that the PCBPs are involved in a remarkable array of biological processes+ Members of this protein family are linked to mRNA stabilization (Weiss & Liebhaber, 1994Holcik & Liebhaber, 1997), translational silencing (Ostareck et al+, 1997;Collier et al+, 1998), and translational enhancement (Blyn et al+, 1997;Gamarnik & Andino, 1997)+ These proteins also appear to be involved as determinants of transcriptional controls (Michelotti et al+, 1996;Tomonaga & Levens, 1996) and apoptotic pathways (Charroux et al+, 1999;Zhu & Chen, 2000) and constitute candidate structural components of recombination complexes within retrotransposon long terminal repeats (Goller et al+, 1994) and in telomere complexes (Lacroix et al+, 2000)+ The common denominator of PCBP activities appears to reflect binding to C-rich single-strand motifs+ Determining how such interactions might factor into this broad array of diverse biologic functions constitutes a major challenge to current research efforts+ Initial studies of PCBPs have been previously reviewed Ostareck-Lederer et al+, 1998)+ This article will focus with particular attention on three areas of recent interest: (1) identification and characterization of novel PCBP isoforms and posttranslational modifications that may underlie their functional diversity; (2) new insights into the evolutionary history of the PCBPs that may shed light on their conserved structure-function relationships, and (3) the expanding spectrum of PCBP functions in transcriptional and posttranscriptional controls+…”
Section: Perspectivementioning
confidence: 99%
“…PCBPs have been implicated in a wide spectrum of posttranscriptional controls+ Initial insights into the roles emerged from studies of human a-globin mRNA stabilization (Weiss & Liebhaber, 1994+ Highlevel stability of a-globin mRNA is essential to full expression of globin proteins during the 2-3 days of transcriptionally silent terminal erythroid differentiation+ Stabilization of a-globin mRNA is tightly linked to formation of a binary complex between a single molecule of aCP and a pyrimidine-rich motif within the a-globin 39 UTR ("a-complex"; Fig+ 4A; Kiledjian et al+, 1995;Wang et al+, 1995;Chkheidze et al+, 1999)+ Interruption of any of the three C-rich patches within this region disrupts the a-complex assembly in vitro and decreases a-globin mRNA stability in vivo (Wang et al+, 1995;Weiss & Liebhaber 1995)+ aCP-1 and aCP-2 can independently bind to the human a-globin mRNA 39 UTR to form the a-complex as demonstrated in vitro+ This binding is specific to aCPs as hnRNP K lacks this binding activity (Chkheidze et al+, 1999)+ The respective K d values of recombinant aCP-1 (51 nM) and aCP-2 (0+8 nM) FIGURE 4. Examples of functions mediated by the PCBPs+ Six distinct examples of PCBP function are shown+ In each case, the PCBP isoform of interest is indicated as a filled circle+ A specific example is given for each of these indicated functions and each is expanded upon in the text+ The mRNAs are indicated in diagrammatic format with tick marks indicating the initiation and termination codons+ The cellular mRNAs are also shown with cap (filled circles) and poly(A) tails+ The polioviral mRNA lacks a cap structure; the two IRES structures of specific interest, secondary structures known as Domain I and Domain IV, are shown+ Question marks indicate unidentified protein factors and/or assumed protein-protein interactions (as discussed in the text)+ 272…”
Section: Stabilization Of Cellular and Viral Mrnasmentioning
confidence: 99%
“…A single base substitution in the human a-globin mRNA termination codon, the ConstantSpring mutation, allows the read-through of the translating ribosome into the 3'UTR and leads to destabilization of the mRNA, presumably by displacement of the a-complex (Weiss and Liebhaber, 1994). Interestingly, analysis of the a−complex composition identified hnRNP E1 and hnRNP E2, also known as aCP1 and aCP2, as the main components (Kiledjian et al, 1995) (Fig.…”
Section: Stabilization Of A-globin Mrna During Erythropoiesismentioning
confidence: 99%